Analog Filters - Su, Kendall. (Springer US, 2002)
Analog Filters, Second Edition covers four major fundamental types of analog filters - passive, op amp-RC, switched-capacitor, and operational transconductance amplifier-capacitor (OTA-C). (The last of these types is the major addition in the Second Edition). The emphasis is on the fundamental principles and theory of analog filters. It is targeted toward readers in telecommunications, signal processing, electronics, controls, instrumentation, bioengineering, etc. It introduces the reader to the elegant theory in the development of analog filters. Although some of the mechanical steps for generating filters are covered, the book stresses the mathematical bases and the scholastic ingenuity of analog filter theory. It should be helpful to nonspecialist electrical engineers to gain a background perspective and some basic insight to the development of real-time filters. In many modern advances in signal processing, their concepts and procedures have close links to analog filters. The material in this book will provide engineers with a better perspective and more penetrating appreciation of many modern signal-processing techniques. Also by Kendall Su: Handbook of Tables for Elliptic-Function Filters, ISBN 0-7923-9109-8.